Penerapan Log Analyzer untuk Mengetahui Lalu Lintas Jaringan berbasis Elasticsearch, Logstash, dan Kibana - Muhammad Jafier Rama Putra; Henry Saptono (Jurnal Informatika Terpadu, 2022)
Recent advances in information technology have changed the way people view the development of existing applications or networks. New information technology intends to help people divert time and energy to other jobs in their daily lives. What is needed for information technology is management, maintenance, and monitoring. Management, maintenance, and monitoring of information technology or computer networks and the services expected to run as expected by individuals, organizations, or institutions to assist and support work processes within the organization. This research intends to implement a log analyzer and network traffic data based on ELK Stack (Elasticsearch Logstash Kibana), which can send logs, collect logs and visualize logs from the server. The implementation of the log analyzer and network traffic data in this study uses Ubuntu 18.04 Server and Ubuntu 18.04 as a client. The results of testing the implementation of the log analyzer and network traffic data that have been carried out with a success rate of 100% show that all log tests that occur on the server can be sent in real-time to the central server of the ELK Stack.